(untitled) (Південний архів (історичні науки), 2023)
The aim is to examine the activities of O. Lutskyi in ensuring the functioning of representatives of the Ukrainian community in representative authorities of Poland in 1928–1930s. The stated purpose involved analyzing the following research tasks: O. Lutskyi’s participation of O. Lutskyi in the pre-election campaign for the Polish Sejm in 1928, activities of O. Lutskyi as an ambassador of the Polish Sejm. The methodological basis of the research was concrete-historical, comparative and historical-analytical methods. The principles of objectivity, historicism, multifactoriality are used. Results and conclusions. In the course of the conducted research, it was established that O. Lutsky chose for himself the path of struggle for the revival of Ukrainian statehood by political methods. He advocated the idea of forming a unified Ukrainian national front, which was an effective tool for gaining the political sovereignty of the Ukrainian people. During the 1928 Polish parliamentary election O. Lutskyi insisted on the creation of both a joint Ukrainian national electoral bloc and an electoral bloc of national minorities of the Polish state. He considered the elections as an opportunity to carry out legal propaganda of Ukrainian ideas, which will contribute to the consolidation of Ukrainians. It was stated that despite the obvious loss of a certain number of mandates due to the repression of the Polish authorities, he believed that the participation of Ukrainian political organizations in the elections was necessary. For Ukrainian society, its elected officials in local authorities and the Polish parliament were the representatives and defenders of the interests of the national community both before the Polish authorities and in the international arena. In the Polish parliament, O. Lutskyi practically implemented what he talked about during the elections: he built Ukrainian national life in his district, defended the economic interests of Ukrainian voters, and at international forums sought the right of the Ukrainian people to self-determination.